Comparing eating behaviours, and symptoms of depression and anxiety between Spain and Greece during the COVID‐19 outbreak: Cross‐sectional analysis of two different confinement strategies. (4th August 2020) - Papandreou, Christopher; Arija, Victoria; Aretouli, Eleni; Tsilidis, Konstantinos K.; Bulló, Mònica
Abstract: Objective: We compared eating behaviours, and depressive and anxiety symptoms in two countries with different confinement strictness strategies and different levels of COVID‐19 pandemic. Method: A web‐based cross‐sectional survey was administered during and shortly after the COVID‐19 related lockdown in Spain and Greece. Multivariable linear regression analyses were performed to identify country differences associated with eating behaviour, and symptoms of depression and anxiety. Results: This study included 1, 002 responders in Spain and 839 in Greece. The mean ± SD of restraint, emotional and external eating was 2.5 ± 0.79, 2.1 ± 0.81 and 2.6 ± 0.65 in Spain, whereas 2.7 ± 0.85, 2.3 ± 0.99 and 2.9 ± 0.74 in Greece. Spanish participants had lower average scores of restraint and external eating compared to Greek participants ( p < .001), but no difference was seen for emotional eating. In Spain, 13.6%, and 12.3% of the survey respondents reported moderate to severe depressive and anxiety symptoms, respectively, whereas in Greece the respective values were 18.8 and 13.2%. After adjusting for several risk factors, a higher prevalence of anxiety symptoms was observed in Spain compared to Greece ( p = .001), but no difference was seen for depressive symptoms. Conclusions: This study demonstrated high scores of inappropriate eating behaviours and a high frequency of depressive and anxiety symptoms in two Mediterranean countries during the COVID‐19 outbreak. Our findings revealed that compared to Greek participants, Spanish participants, that faced more severe COVID‐19 pandemic and stricter lockdown measures, were associated with lower restraint and external eating and increased anxiety symptoms, but not with depressive symptoms or emotional eating.